FIDIC General Conditions / Payments Clause FIDIC refers to (Fédération Internationale Des Ingénieurs Conseils) (Asian Business Research, 2017)
For any international construction project, Contract is one of the major documents for construction industry. FIDIC General Conditions are the most common used all over the world. Payments term is very important clause and all the project team members need to be aware completely about it. Thus, this paper is considering illustrated payments clauses by flow chart technique to ensure that all the engineers are handling easily those terms. Without real understanding of those clauses usually the project will get cash flow tribbles.